5-Azacytidine in chronic myelomonocytic leukemia: case report and review of literature - Mariangela Greco; Marianna Criscuolo; Luana Fianchi; Livio Pagano; Maria Teresa Voso (Mediterranean Journal of Hematology and Infectious Diseases)
Hypomethylating drugs are useful in the management of Myelodysplastic syndromes, but  there are only few reports on chronic myelomonocycitic (CMML) leukemia patients. We describe our experience in 3 CMML patients treated with azacitidine. Two patients obtained partial response after 4 treatment cycles with only minor toxicity and are in continuous partial response, with stable peripheral blood counts, at 29 and 30 cycles from treatment start.